DEL FÚTBOL A LA METÁFORA DE LA COTIDIANIDAD - Segura Soto, Gustavo Adolfo (2012)
From the soccer football jargon raises some expressions that have been inserted into our everyday life naturally. In that interim, going to soccer football to the daily communication between unaware people to soccer football, it experiences a metaphor translation, in which the usage transforms itself into something that is not the same as the original. As a consequence, the lexical changes occur not only in meaning due to another communicative situation (and another contextual use) but also keeping the same direct reference related to the soccer football.